Singing off the same hymn sheet? Examining coherence in a talent development pathway (part 1). Issue 15 (3rd August 2021) - Curran, Orlaith; MacNamara, Áine; Passmore, David
ABSTRACT: Although there is research available into successful Talent Development Environments (TDEs), the data mostly reflects TDEs in elite academies, national groups or in a single successful club. This literature provides insight into the positive characteristics that are commonplace in these effective TDEs. However, little is known about the TDE surrounding an entire amateur national organization where athletes regularly compete across multiple teams, simultaneously representing at both domestic and international level. Importantly this added complexity increases the number of stakeholders across the pathway (e.g., school, club, international) creating a need for coherence throughout the TDE. Additionally considering the lack of research relating to females in talent development, we were interested from a pragmatic view, in examining the TDE of an amateur national hockey organization where young female athletes must navigate the pathway while simultaneously playing on multiple teams, contending with various coaches and contexts. The results suggest that the TDE provides a long term development experience supplemented with a good support network across all contexts. However, the alignment of expectations across contexts and the quality preparation of athletes in this TDE requires more attention to facilitate effective holistic athlete development.